Influence of Work Environment, Organizational Culture, and Providing Incentives on Employee Work Spirit at Syantikara Foundation - Destika Dwi Nur Azizah; Kusuma Chandra Kirana; Tri Ratna Purnamarini (Admisi dan Bisnis, 2026)
The abstract is this study aims to investigate now of work enviroment , organizational culture, and insentif affect at Yayasan Syantikara employees work spirit. This study used a quantitative methodology with information gathered from 56 employees. A likert scale was used to collec data, and multiple regression was used for analysis. The results showed that employees were significantly positively influenced by the work environment and organizational culture.  that the work environment and organizational culture have a significant positive impact on employees’ work spirit. Together, the work environment, organizational culture, and insentif significantly affect employees’ spirit. The results indicate that improving the effectiveness of the insentif system is necessary to maximize its impact. The results may not be as broadly applicable as they could be because this study was restricted to a single foundation and had a small sample size.